94.2k views
4 votes
-3(5x + 7) + 2x – 3 = 5.x - 8 - 13​

2 Answers

1 vote

Answer

x=-1/6

or

x=0.1 6¯

Explanation:

User Krosenvold
by
4.5k points
4 votes

Answer:

x=-7

Explanation:

Simplifying

3(x + -2) = 5x + 8

Reorder the terms:

3(-2 + x) = 5x + 8

(-2 * 3 + x * 3) = 5x + 8

(-6 + 3x) = 5x + 8

Reorder the terms:

-6 + 3x = 8 + 5x

Solving

-6 + 3x = 8 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.

-6 + 3x + -5x = 8 + 5x + -5x

Combine like terms: 3x + -5x = -2x

-6 + -2x = 8 + 5x + -5x

Combine like terms: 5x + -5x = 0

-6 + -2x = 8 + 0

-6 + -2x = 8

Add '6' to each side of the equation.

-6 + 6 + -2x = 8 + 6

Combine like terms: -6 + 6 = 0

0 + -2x = 8 + 6

-2x = 8 + 6

Combine like terms: 8 + 6 = 14

-2x = 14

Divide each side by '-2'.

x = -7

Simplifying

x = -7

User JustTrying
by
4.9k points